The Effect of Problem-Posing Learning Method on Students Achievement in Reading Invitation Letter - Mutia Nasution; Syahroni Hasan Siregar (research, training and philanthropy institution Natural Aceh, 2021)
The aims of this research is to know if there is a significant effect of problem-posing learning method on students’ achievement in reading invitation text of the twelfth grade students of SMA Negeri 1 Sipirok. The population is the twelfth grade students of SMA Negeri 1 Sipirok, which is consist of 190 students. Then, the sample is taken from the population by cluster random sampling technique and the total sample is 79 students. The writer uses experimental method. After calculating the data, it is found that the mean score of students reading invitation letter before taught by Problem Posing learning method is 68; it is categorized “enough”. While the mean score of students reading invitation letter after taught by Problem Posing learning method is 79, it is categorized “good”. After finding the score of ttest and ttable, both of the scores are compared. It is found that ttest is higher than ttable (ttest > ttable = 15.71 > 2.04). It means there is significant effect of Problem Posing learning method on reading invitation letter of the Twelfth grade students of SMA Negeri 1 Sipirok. So, the hypothesis in this research can be accepted